Sugarcane Bagasse-derived Hydrochar: Modification with Cations to Enhance Phosphate Removal: 10.32526/ennrj/19/202100036 - Thawornchaisit, Usarat; Onlamai, Tanrawee; Phurkphong, Nontakorn; Sukharom, Rawiwan (Environment and Natural Resources Journal, 2021)
Cation modified hydrochars were synthesized by hydrothermal carbonization (HTC) of sugarcane bagasse, followed by impregnation of three different cations (Ca, Mg, and Fe) or co-precipitation of Fe3+ and Fe2+. HTC enhanced the hydrochar surface area and increased the enrichment of oxygen functional groups on the hydrochar surface confirmed by FTIR. The oxygen functional groups further improve the adsorption capacity for cations during hydrochar chemical modification. Physical appearance, FTIR and XRF confirmed that Ca2+, Mg2+ and Fe2+ or Fe3+ were well retained in the bagasse-derived hydrochar. The pHpzc values of all chemically modified hydrochars were greater than the unmodified hydrochar or bagasse alone. Modification with different cations improved phosphate uptake capacity. The Fe-modified hydrochar with about 45-50% Fe content showed greater phosphate removal efficiency than Ca- and Mg-modified hydrochars. In addition, hydrochars decorated by impregnation of Fe3+ demonstrated better phosphate removal than ones produced by co-precipitation of Fe3+ and Fe2+. Thus, chemically modified hydrochars could be used as an environmentally alternative adsorbent for phosphate removal from aqueous solutions.